2022 Global food policy report: Climate change and food systems - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Climate change threatens our food systems and the multiple development goals linked to sustainable food system transformation. Action is urgently needed, both to increase adaptation and resilience and to achieve major emissions reductions. Current efforts must be stepped up and greatly expanded to ensure food security, nutrition, and well-being for all in the years to come. The 2022 Global Food Policy Report showcases opportunities for accelerating innovation, reforming policies, resetting market incentives, and increasing financing for sustainable food systems transformation, as well as promoting healthy diets and building resilience.